Use of nurse endosperm for the culture of haploid embryos produced by durum wheat x maize crosses - Sahli , Anissa; Ltifi , Ali; Mansouri , Sonia; Haouala , Faouzi (Emirates Journal of Food and Agriculture, 2023)
The use of doubled-haploids in plant breeding programs enables accelerating the release of new varieties adapted to climate change. The durum wheat x maize crosses technique is a method of choice for producing durum wheat haploid plants. The haploid embryos produced by this method develop without albumen and their survival is ensured by post-pollination hormonal treatments. In this study, nine post-pollination treatments with 2,4-Dichlorophenoxyacetic acid (2,4-D), Picloram and Dicamba at the concentrations of 10, 50 and 100 mg.L-1 were applied to 7 durum wheat genotypes. The effects of genotype and post-pollination treatment on durum wheat haploid embryos produced by durum wheat x maize crosses and the use of the endosperm nursing technique for haploid plantlets regeneration were investigated. The haploid induction parameters varied with the durum wheat genotypes as well as the post-pollination treatments. The phenomenon of polyembryony resulting from durum wheat x maize crosses is reported for the first time in this article. The durum wheat genotypes showed different abilities to produce monoembryo and polyembryos. The post-pollination treatments with 2,4-D (10 mg.L-1) and Picloram (10 and 100 mg.L-1) gave a higher embryo formation frequency than the treatments with Dicamba. The embryo conversion to plantlet was greatly improved, especially in recalcitrant genotypes using the durum wheat endosperm as supplemental nourishment in combination with the Gamborg B5 regeneration medium. Keywords: Durum wheat; Haploid embryo; Maize; Nurse Endosperm Technique; Polyembryony